Wirtualny zespół w kontekście zróżnicowania kulturowego - Żukowska, Joanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper deals with virtual team in the context of cultural differences. It presents problems faced by the team. The paper presents reasons and origin of these differences. It shows how different team members coming from different cultures influence the team functioning which is accomplishing common goal. It also shows the sources of conflicts in virtual team and suggests methods of resolving it. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 420-428